2019
DOI: 10.2166/ws.2019.030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical characteristics and water quality assessment of shallow groundwater: a case study from Linhuan coal-mining district in northern Anhui Province, China

Abstract: Major ion and trace element concentrations in shallow groundwater of Linhuan coal-mining district, Northern Anhui Province, China, were analyzed to determine its hydrogeochemical characteristics and to assess drinking and irrigation water quality. The relative abundance of cations and anions was Na+ > Mg2+ > Ca2+ > K+, and HCO3− > SO42− > Cl− > NO3−, respectively. The concentrations of Na+, HCO3−, NO3−, and total dissolved solids (TDS), and the electric conductivity (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The natural rivers and lakes are commonly controlled significantly by evaporation [35]. Taking the shallow groundwater around Suzhou city as the research object, it is concluded that rock weathering is the main source of ions in this area [15]. However, in this study, the hydrochemical formation mechanism of surface water is similar to that of groundwater, indicating the interaction between groundwater and surface water.…”
Section: Processes Controlling River Solutementioning
confidence: 60%
See 1 more Smart Citation
“…The natural rivers and lakes are commonly controlled significantly by evaporation [35]. Taking the shallow groundwater around Suzhou city as the research object, it is concluded that rock weathering is the main source of ions in this area [15]. However, in this study, the hydrochemical formation mechanism of surface water is similar to that of groundwater, indicating the interaction between groundwater and surface water.…”
Section: Processes Controlling River Solutementioning
confidence: 60%
“…Correlation analysis was conducted on the nutrition indicators (TP and TN) and major hydrochemical parameters of surface water in the study area, and the results are shown in Figure 7. Because the shallow groundwater in the study area is usually about three meters deep, surface water replenishes groundwater during the rainy season and shallow groundwater replenishes the river during the dry season [15].As can be seen from Figure 7a, Ca 2+ had a good correlation with Mg 2+ , F − , Cl − , SO4 2− , and HCO3 − , indicating the diversity of sources of calcium ions. However, in Figure 7b, Ca 2+ are not well correlated with other water quality parameters; this may indicate the monotony of Ca 2+ source in the Tuo River.…”
Section: Correlation Analysis Of Water Quality Parametersmentioning
confidence: 89%
“…This area has a high population density and groundwater is used for both various human requirements and irrigation. In the process of coal mining, gangue, domestic wastewater, and agricultural non-point source pollution affect the hydrogeochemical characteristics of shallow groundwater; this can lead to organic or inorganic pollution and threaten groundwater quality and water supply security [41]. The groundwater aquifer systems in the mining area can be categorized as follows: loose pore, coal measure fractured, carbonate fractured, and interstitial aquifer systems.…”
Section: Research Areamentioning
confidence: 99%
“…The area contained 19 coal mines with a total production capacity of 30.00 million t/y [33,34]. After 69 years of mining, a large number of collapsed ponds and coal gangue piles have accumulated on the land surface [35]. Aside from the mining area, most of the land in this area is dedicated to agriculture where wheat and corn are the primary crops.…”
Section: Regional Geology and Hydrogeologymentioning
confidence: 99%